PERAN GURU PAI DALAM MENUMBUHKAN SIKAP SOSIAL SISWA SMA NURUL IMAN PALEMBANG - Muhammad Febriansyah; Ahmad Wahyu Hidayat (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
This research included in the research field (Field Resarch) are purely qualitative. As for the subject of the study i.e. principals, Islamic education, Teachers and students of class X SMA NURUL IMAN Palembang. While the collection of data in this study using the method of observation, in-depth interviews and documentation. The analysis in this study uses data reduction techniques, presentation of data and verification. The results of this research is to 1). There is a positive and significant role of competence education teachers of Islamic religion in fostering social attitude 2). The attitude of Social discipline and cooperation of students is already good, disciplined students already in the school and the role of Teacher Education coupled with the religion of Islam to be quite good. 3.) factor endowments in the cultivation of the social attitudes of HIGH SCHOOL students at NURUL IMAN Palembang was school rules or code of conduct compulsory school students observe, the teacher shows a great attitude towards students, teachers reprimand students whenever students are less invited to well, as well as the teacher always invites students to cooperate in maintaining and cleaning up the environment of the school.